3D Printing: Decal Electronics: Printable Packaged with 3D Printing High‐Performance Flexible CMOS Electronic Systems (Adv. Mater. Technol. 1/2017). Issue 1 (January 2017) - Sevilla, Galo A. Torres; Cordero, Marlon D.; Nassar, Joanna M.; Hanna, Amir N.; Kutbee, Arwa T.; Arevalo, Arpys; Hussain, Muhammad M.
Abstract : In article number 1600175, Muhammad M. Hussain and co‐workers report a highly manufacturable heterogeneous integration strategy to combine complementary metal oxide semiconductor electronics, inkjet printing for interconnection, 3D printing for packaging, and roll‐to‐roll printing of decal electronics. The flexible electronic system shows reliable electrical performance, large‐scale integration density as well as multifunctionality under extreme mechanical conditions.